Interest rate pass-through to the rates of core deposits: A new perspective - Heiko Sopp (Deutsche Bundesbank, 2018)
Within a Salop framework, this paper shows that banks' profit smoothing can explain incomplete pass-through of market rates to the rates of core deposits. Using time series data of deposit and lending rates of local German banks, this paper will show that local banks pass through return variations to their depositors. To the degree to which market rates influence new business lending rates, there is, therefore, an indirect channel through which market rates affect the rate of core deposits. In the absence of capital market alternatives for core deposits, this indirect channel explains why changes in the market rate affect the rate of core deposits only slowly and fractionally.
Keywords: G21; E43; 330; interest rate pass-through